Theft a love story - Carey, Peter 1943- (Knopf, 2006)
"From the two-time Booker Prize-winning author and recipient of the Commonwealth Prize comes this new novel about obsession, deception, and redemption, at once an engrossing psychological suspense story and a work of highly charged, fiendishly funny literary fiction. " From the bookjacket.
Keywords: Artists -- Australia -- Fiction; Painting -- Forgeries -- Fiction; Australien; Love stories